Rekenaars as 'n hulpmiddel in verpleegkundige administrasie - M. Coetsee (AOSIS, 1984)
Over the last few years pressure has been brought to bear on nurse managers worldwide to cut costs in their departments and to freeze posts, while maintaining a high quality of nursing care. Computers can be utilised in nursing administration to cut costs and to help increase productivity. There are three main areas in which computers can serve as an aid to nursing administration. A word-processor in the manager's office can save a lot of time, the spreadsheet is invaluable for financial planning and a data base, which can be likened to an electronic filing cabinet, quickly produces information which would previously have taken hours to compile. There are computer programs, such as the Nurse Manager which are designed specifically for nursing administration, the above program combines the latest micro-computer technology with a patient classification system to provide a powerful staff management tool.